Penerapan Model Pembelajaran STAD dan NHT Together Untuk Meningkatkan Hasil Belajar Matematika Kelas IV SDN Kelayan Selatan 3 Kota Banjarmasin - Ramadhani, M. Ihsan (Yayasan Pendidikan Internasional Bengkulu, 2023)
The purpose of this study was to determine the quality of teacher activity, student activity and to improve student learning outcomes in mathematics learning. This study used a qualitative research approach with the type of Classroom Action Research (PTK). The setting of this research was carried out at SDN Kelayan Selatan 3 Banjarmasin City in even semester with a total of 20 students. Data collection techniques in this study are qualitative data and quantitative data, which are obtained through observation of teacher activities, observation of student activities, and learning outcomes through evaluation tests. Data analysis with descriptive analysis techniques presented in tables interpreted with percentages and indicators of learning completeness set. The results showed that the quality of teacher activity from teacher activity in implementing learning through a combination of Student Teams Achivement Division (STAD) and Numbered Heads Together (NHT) learning models on the material of the perimeter and area of flat shapes in class IV SDN Kelayan Selatan 3 Banjarmasin Even Semester with a score of 29 achieved very good criteria. Student activity in learning the material of the perimeter and area of flat shapes through a combined learning model of Student Teams Achivement Division (STAD) and Numbered Heads Together (NHT) in class IV SDN Kelayan Selatan 3 Banjarmasin Even Semester with a score of 90% reaching very good criteria. There was an increase in the learning outcomes of grade IV students on the concept of properties of flat shapes through a combination of Student Teams Achivement Division (STAD) and Numbered Heads Together (NHT) learning models in grade IV SDN Kelayan Selatan 3 Banjarmasin Even Semester with the completeness of student learning outcomes reaching 100% of the number of students who participated in the learning.